Strategi Dakwah Karimah Remaja Masjid Raya Mujahidin Pontianak: Strategi Dakwah - Widia Permatasari (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2022)
Abstract: This research is a study of the KARIMAH (Rutin Muslimah) Da'wah Strategy for Youth at the Great Mosque of Mujahidin Pontianak. The strategy includes a management process consisting of management functions that are the focus of this research, including: The aims of this research are: 1) planning; 2) implementation in the form of socialization, cooperation and methods; and 3) evaluation. To explore this research, the researcher used a qualitative approach. data collection methods in the form of observation, interviews, and documentation. Based on the results of the study, the researchers concluded that: 1) the planning carried out by Mujahidin Youth in the field of women was determining the presenters, materials, and schedule of activities. This activity is in accordance with the needs of today's youth and Muslim women with the concept of providing gifts or door prizes. 2) the implementation carried out by Mujahidin Youth in the field of women is socialization (invitation for information on activities about routine Muslim women studies from social media such as Facebook and Instagram), collaboration with related parties, namely SALIMAH and Orchi Chicken. From the results of cooperation in The Female Field with SALIMAH, The Female Field gets a presenter who will be determined by SALIMAH to fill KARIMAH's da'wah activities, and from the collaboration in The Female Field with Orchi Chicken, namely The Female Field, a free meal voucher is given in the implementation process such as materials and door prizes provided is part of the da'wah method. The da'wah method used is the lecture method, the story method, oral-humor method, the question, and answer method, and the coupon method (sponsorship).